Dampak Investasi, Proyek dan Utang Luar Negeri Terhadap Kemiskinan Indonesia Tahun 2010-2020 - Anas Fadhillah; Arintoko Arintoko; Kamio Kamio (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study is to analyze the acceleration of poverty alleviation through investment, projects, and foreign debt from the United States, the Netherlands, China and Japan on Indonesian Poverty in 2010-2020. The technique used in the study used panel data regression. The data used in the study of poverty variables, investment variables, projects, foreign debt. Data analysis was taken from the Central Statistics Agency in 2010-2020. Based on the Chow Test and the Hausman Test, this analysis was chosen to be the Fixed Effect Model and has passed the assumptions of the classical test. The results show that investment and projects have a significant negative effect on poverty and foreign debt has no significant effect on society, which means investment, projects, poverty in Indonesia. Based on the results of this study, the implications of this study are that the central government, local governments, Bank Indonesia and related institutions increase investment and foreign projects by establishing good relations with friendly countries, facilitating investment licensing in Indonesia, good foreign debt by prioritizing growth. Economy and poverty alleviation.